2015
DOI: 10.1039/c4ra16637j
|View full text |Cite
|
Sign up to set email alerts
|

Development of hybrid composites for automotive applications: effect of addition of SEBS on the morphology, mechanical, viscoelastic, crystallization and thermal degradation properties of PP/PS–xGnP composites

Abstract: The presence of SEBS and xGnP in PP/PS blend allows better stress transfer between the phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…From the table, it is obvious that the thermal stability of the composites increases in the presence of MWCNTs. In our previous publications, we reported that incorporation of nanofillers only marginally improve the thermal stability of immiscible and incompatible multiphase systems . However, in the present case, a considerable enhancement in thermal stability is observed by the addition of even 0.1% by weight of MWCNTs.…”
Section: Resultscontrasting
confidence: 55%
“…From the table, it is obvious that the thermal stability of the composites increases in the presence of MWCNTs. In our previous publications, we reported that incorporation of nanofillers only marginally improve the thermal stability of immiscible and incompatible multiphase systems . However, in the present case, a considerable enhancement in thermal stability is observed by the addition of even 0.1% by weight of MWCNTs.…”
Section: Resultscontrasting
confidence: 55%
“…The absence of unsaturations in the hydrogenated structure provides excellent thermal and UV resistance [31], which is a key factor in the food packaging industry. In addition, due to its wide range of elasticity and hardness values (depending on the ethylene-butylene segments) and easy processing at relatively low temperatures, it is used in a wide range of sectors such as adhesives, cable coatings, films, toys, household appliances and, increasingly, in the medical and automotive sectors [32,33]. SEBS has been reported to provide improved impact strength and overall ductility in poly(propylene)/poly(styrene) blends as well as in polyamide-based formulations [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Styrene-b-(ethylene-co-butylene)-b-styrene elastomer (SEBS) is the product of a hydrogenated polystyreneb-polybutadiene-b-polystyrene (SBS) triblock copolymer, and exhibits an excellent oxidative and hydrolytic resistance. 5 The advantages of SEBS makes it a potential candidate for the preparation of plasticizer-free bags. 6 However, long-term contact of red blood cells (RBCs) with SEBS induces serious hemolysis, and can cause intrinsic mechanisms for human disease.…”
Section: Introductionmentioning
confidence: 99%